2017
DOI: 10.1177/0145445517724539
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders Among Veterans With Posttraumatic Stress Disorder: A Pilot Study

Abstract: Effective treatment options are needed for veterans who do not participate in trauma-focused psychotherapy. Research has yet to examine the effectiveness of transdiagnostic psychotherapy in veterans with posttraumatic stress disorder (PTSD) and co-occurring psychological disorders. This pilot study examined the effectiveness of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders (UP) delivered in a 16-week group format. We examined treatment outcomes in male and female veterans ( n = 52) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 57 publications
3
29
0
Order By: Relevance
“…Preliminary evidence supports the effectiveness of the Renfrew Unified Treatment Model in reducing ED symptoms and improving transdiagnostic outcomes in the current setting (Thompson‐Brenner et al, 2019). In addition, recent findings support the effectiveness of the UP for individuals with primary PTSD and veterans treated in a primary care setting (De Paul & Caver, 2020; Varkovitzky et al, 2018). Residential treatment following Unified Treatment Model typically lasts for about 4 weeks (sample mean length of stay = 33.28 days) and consists of individual and group psychotherapy, meals, and support from psychiatric practitioners and dieticians (for more details, see Thompson‐Brenner et al, 2018).…”
Section: Methodsmentioning
confidence: 79%
“…Preliminary evidence supports the effectiveness of the Renfrew Unified Treatment Model in reducing ED symptoms and improving transdiagnostic outcomes in the current setting (Thompson‐Brenner et al, 2019). In addition, recent findings support the effectiveness of the UP for individuals with primary PTSD and veterans treated in a primary care setting (De Paul & Caver, 2020; Varkovitzky et al, 2018). Residential treatment following Unified Treatment Model typically lasts for about 4 weeks (sample mean length of stay = 33.28 days) and consists of individual and group psychotherapy, meals, and support from psychiatric practitioners and dieticians (for more details, see Thompson‐Brenner et al, 2018).…”
Section: Methodsmentioning
confidence: 79%
“…), there is need to develop transdiagnostic treatments that can simultaneously address PTSD and its common overlapping comorbities. 12,13 Psychedelic drugs demonstrate potential as transdiagnostic treatment approaches for the Veteran population. Psilocybin, lysergic acid diethylamide (LSD), and 3,4methylenodloxymethamphetanine (MDMA) are the most widely researched psychedelic-assisted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…), there is need to develop transdiagnostic treatments that can simultaneously address PTSD and its common overlapping comorbities. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…So far, studies exploring the effectiveness of the UP in a group format have led to promising findings [ 12 15 ].Overall, results suggest that the UP obtains medium-to-large effect sizes on numerous outcomes, including depression, anxiety, positive and negative affect, quality of life, overall adjustment, and avoidance of negative sensations, for both anxiety and mood disorders [ 12 14 ]. These studies have also revealed that between half and two thirds of patients ceased to meet diagnostic criteria after the treatment and one investigation, conducted by our team, revealed that changes remained stable 12 months after treatment completion [ 13 ].…”
Section: Introductionmentioning
confidence: 99%